Determining the Role of Life Style Factors in Male Reproductive Functions - Bansal, Amrit Kaur; Cheema, Ranjna S. (Research Aspects in Agriculture and Veterinary Science Vol. 5, 2022)
The prevalence of male and female infertility is being increased in many nations and has emerged as a serious problem. Many life style factors and occupational exposures can have substantial effects on fertility problems. Life style factors such as smoking, illicit drug (cocaine, cannabis), alcohol and caffeine consumption, exposure to extreme heat etc. have negative effects on functions of male reproductive system. In recent years, increase in disorders of male reproductive system may be associated at least some extent with these factors; which are enhanced by some of new emergent life style habits. A detailed study is required based on the data i.e., excess use of mobile phones and impact of mental stress on male reproductive health. This review highlights the role of various life style factors, environmental stresses and occupational exposures in male reproductive functions and their negative feedback in declining semen quality, increased oxidative stress as well as sperm DNA damages in male. Increase in reproductive disorder in male may be correlated at least in part with these factors, which are further added by some of new emergent life styles. Sub-fertile and/or even normal individuals have some control over their reproductive function by adopting healthy lifestyles.